ANALYSIS OF THE IMPACT OF BLOCKCHAIN INTEGRATION, REGULATORY COMPLIANCE TECHNOLOGY, AND ACCOUNTANTS' TECHNOLOGICAL COMPETENCE ON TRANSPARENCY AND EFFICIENCY IN PUBLIC SECTOR ACCOUNTING IN INDONESIA - Natong, Asriani; Aulia, Triana Zuhrotun; Sudarmanto, Eko (Gapenas Publisher, 2025)
This study investigates the impact of blockchain integration, regulatory compliance technology, and accountants’ technological competence on transparency and efficiency in public sector accounting in Indonesia. Employing a quantitative research design, data were collected from 130 public sector accountants and financial management staff using a five-point Likert scale questionnaire. The data were analyzed using Structural Equation Modeling – Partial Least Squares (SEM-PLS 3). The results reveal that blockchain integration and regulatory compliance technology significantly enhance transparency and efficiency in public sector accounting. Moreover, accountants’ technological competence plays a vital role in reinforcing these relationships by enabling more effective utilization of digital tools and systems. These findings emphasize that technological innovation, when combined with human capability, contributes to improved governance, accountability, and operational performance in Indonesia’s public sector. The study highlights the necessity for public institutions to invest not only in digital transformation but also in continuous professional training to strengthen financial transparency and efficiency.